The inhibitory effects of inulin biopolymers on the seeded growth of hydroxyapatite - Dogan, Oezlem; Oner, Mualla; Cinel, Oezge (CERAMIC SOC JAPAN-NIPPON SERAMIKKUSU KYOKAI, 2010)
In this work crystallization kinetics of hydroxyapatite (HAP) were investigated in the presence of a biodegradable, environmentally friendly polysaccharide-based polycarboxylate, carboxymethyl inulin (CMI), under strictly controlled temperature, pH, and atmospheric conditions. The constant-composition method has been used to study the influence of biopolymers of crystal growth of HAP, on HAP seed crystals at pH 7.4 and 37 degrees C. The results indicate that polymer concentration and the larger number of negatively charged functional groups markedly affect the growth rate. Biopolymer affects the coherence length of the crystalline domain. The decrease in growth rates was substantiated by SEM which showed smaller crystal sizes as a function of increasing carboxylation degree of the CMI and its concentration. (C)2010 The Ceramic Society of Japan. All rights reserved.
Keywords: Hydroxyapatite; Biopolymer; Crystallization; Biomineralization; DICALCIUM PHOSPHATE DIHYDRATE; CRYSTAL-GROWTH; OCTACALCIUM PHOSPHATE; CARBOXYMETHYL INULIN; CONSTANT COMPOSITION; CALCIUM-PHOSPHATE; PRECIPITATION; KINETICS; POLYELECTROLYTES; Materials Science